1
$\begingroup$

One of the steps in my textbook is $$\sum_{k=1}^nk(k-1)+k\binom{2n-2k}{2}=2\sum_{k=1}^nk^3-(4n-2)\sum_{k=1}^nk^2+(2n^2-n-1)\sum_{k=1}^nk$$

I do not know how to go from LHS to the RHS

$\endgroup$
3
$\begingroup$

Expand the binomial $$\begin {align} k(k-1)+k\binom{2n-2k}{2}&=k(k-1)+\frac 12k(2n-2k)(2n-2k-1)\\ &=k^2-k+2n^2k-4nk^2+2k^3-nk-k^2\\ &=2k^3-(4n-2)k^2+(2n^2-n-1)k \end {align}$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.